2021
DOI: 10.1021/jasms.1c00295
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry Imaging of Arabidopsis thaliana Leaves at the Single-Cell Level by Infrared Laser Ablation Atmospheric Pressure Photoionization (LAAPPI)

Abstract: In this study, we show that infrared laser ablation atmospheric pressure photoionization mass spectrometry (LAAPPI-MS) imaging with 70 μm lateral resolution allows for the analysis of Arabidopsis thaliana (A. thaliana) leaf substructures ranging from single-cell trichomes and the interveinal leaf lamina to primary, secondary, and tertiary veins. The method also showed its potential for depth profiling analysis for the first time by mapping analytes at the different depths of the leaf and spatially resolving th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Performing in situ monitoring of individual metabolites has historically been challenging due to the complicated endogenous cellular milieu with high concentrations of complex compounds. ,, This is further complicated by the differences between plant and animal cells since most probes developed for animal cells cannot be immediately applied for plant-based studies. General imaging techniques such as mass spectrometry imaging have been used to overcome these limitations within metabolite research for biomedical applications due to their high sensitivity and multiplex capabilities. , Despite limitations in spatial resolution and tissue damage, they have shown tremendous promise for fast and direct imaging of intracellular molecules without the development of specific probes …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Performing in situ monitoring of individual metabolites has historically been challenging due to the complicated endogenous cellular milieu with high concentrations of complex compounds. ,, This is further complicated by the differences between plant and animal cells since most probes developed for animal cells cannot be immediately applied for plant-based studies. General imaging techniques such as mass spectrometry imaging have been used to overcome these limitations within metabolite research for biomedical applications due to their high sensitivity and multiplex capabilities. , Despite limitations in spatial resolution and tissue damage, they have shown tremendous promise for fast and direct imaging of intracellular molecules without the development of specific probes …”
Section: Discussionmentioning
confidence: 99%
“…11,13 Despite limitations in spatial resolution and tissue damage, they have shown tremendous promise for fast and direct imaging of intracellular molecules without the development of specific probes. 16 Conversely, bulky bioorthogonal probes, such as those with fluorescent tags or click chemistry reactivities, represent highly specific probes with strong potential for multiplex imaging applications. However, large tags often interfere with their endogenous metabolism and localization and potentially their cellular dynamics, hampering their applications in studying metabolic processes.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infrared laser ablation atmospheric pressure photoionization MS (LAAPPI-MS) imaging was employed to conduct metabolite profiling at various layers of Arabidopsis leaf tissues, ranging from trichomes to veins. This demonstrated that the distributions of different flavonol glycosides, fatty acids, fatty acid esters, galactolipids, and glycosphingolipids varied significantly between the different substructures in the leaves [212].…”
Section: Single-cell and Spatial Metabolomicsmentioning
confidence: 91%
“…1c, Supplementary Information Figs. 1-7) [5][6][7] . Between 20 to 30 small molecules were localized per each developmental zone (Supplementary Figs.…”
mentioning
confidence: 99%